THE ANTHROPOGENIC TOURISM POTENTIAL AND ITS CAPITALIZATION POSSIBILITIES IN IARA-HĂȘDATE BASIN - Ciprian MOLDOVAN; Ştefan DEZSI; Raularian RUSU; Titus MAN; Eugen Bogdan DOLEAN (Studia Universitatis Babeş-Bolyai: Geographia, 2020)
The paper deals with the anthropogenic tourism resources of Iara-Hășdate Basin, which are the result of the combining effect of history, development of human civilization and typology and traditions of ethnic groups inhabiting the basin. The result is a unique cultural heritage belonging to both material and spiritual legacy, with visible attractive products for tourism materialized mostly in architecture, clothing, customs, music and gastronomy. The historical evolution of the area is reflected not only by culture, traditions and attitudes of the people towards lifetime events, but also by the relatively high number of tourism attractions from different historical periods, generating iconic architectural, historical and religious landmarks. Considering the complexity of tourism resources available in Iara-Hășdate Basin, there are multiple types of tourism offered by the area. Existing natural conditions favor various forms of recreational mountain tourism from traditional winter leisure tourism, hiking and hunting tourism to more extreme ones like mountain climbing, caving and extreme tourism. The rich historical cultural heritage of the studied area offers very good premises for the development of various cultural tourism forms, mostly rural and religious tourism. The results of tourism resources assessment can be used to coordinate tourism development strategies for a superior endorsement and to better prioritize tourism related policies with a focus on economic development, land use management, territorial identity and environmental quality.